Introduction to special issue: Assimilation, interrupted: Transforming discourses of culture- and honour-based violence in Canada - Mucina, Mandeep; Jamal, Amina (International Journal of Child, Youth and Family Studies, 2021)
This special issue about race, honour, culture, and violence against women in South Asian Canadian communities is proffered as an entry point to a wider, multilayered discussion about race, culture, gender, and violence. It hopes to intensify a debate on gendered violence that could tie in with analysis and commentary on individual killings in family-related sites, murders of racialized women and girls in public sites, and other forms of violence against women and girls in society. We encourage readers to consider how to understand the landscape that South Asian Canadian women and girls are confronting, while also asking critical questions about the wider settler colonial system in which we all participate as we fight gender-based violence.